Original paperThyroid neoplasms – errors of the cytological diagnosis - Jabłoński, Sławomir; Kordiak, Jacek; Bella, Mariusz; Zieliński, Krzysztof Włodzimierz; Jabłonowski, Zbigniew; Santorek, Edyta; Rysz, Jacek (Archives of Medical Science, 2005)
Objectives: the evaluation of the diagnostic value of a cytological examination and its limitations for the diagnosis of thyroid neoplasms. Material and methods: From 1995 to 2004 nine hundred ninety eight patients were operated on for nodular lesions of the thyroid gland in our department. Cytological and histopathologic diagnoses were compared retrospectively in all cases where a neoplasm was suspected (true positive, false negative and false positive diagnoses). The verification was carried out independently by two pathologists. It enabled the establishment of interpretation errors (IE). The cases where cytological and histopathologic diagnoses were incompatible were interpreted as a sampling error (SE). Results: As a result of the verification 45 cytological and histopathologic diagnoses were changed compared with the primary ones. In the analysed material the following diagnoses were put: true positive – 144, true negative – 824, false positive – 12, false negative – 18. The sensitivity of FNAB was 0.89, specificity 0.99, accuracy 0.97 and a positive predictive diagnostic value 0.92. False cytological diagnoses were found in 75 cases (7.5%). In 45 cases (4.5%) a diagnosis was changed compared with a primary one – interpretation error. In the remaining 30 cases (3%) a false diagnosis was caused by a sampling error. Conclusions: FNAB is an examination of high diagnostic value for the detection of thyroid neoplasms in the hands of an experienced pathologist. False cytological diagnoses comprised only a small part (7.5%) of their total number and were caused by interpretation error in 4.5% and by sampling error in 3.0%. The percentage of interpretation errors can be decreased by a multiple independent assessment of samples.